Twelfth Night - Shakespeare, William (Wordsworth Editions, 1993)
Shakespeare's comedy of gender confusion, in which a girl disguises herself as a man to be near the count she adores, only to be pursued by the woman he loves.
Keywords: Drama-Classics (Shakespeare)